TRANSPARENCY OF SOCIAL AND ENVIRONMENTAL DISCLOSURES BY THE TOP FRENCH COMPANIES - Tower, Greg; Ahmad, Raja Adzrin Raja; Pignatel, Isabelle; Hahn, Tobias (The journal of contemporary issues in business and government, 2010)
An investigation of the top 30 French listed companies reveals an overall 50.6% level of communication with small decreases in the social and environmental disclosures in parallel with the deepening economic recession in France. It is argued that the 2001 French regulations may need more rigorous regulatory enforcement and updated requirements consistent with the well known Global Reporting Initiative (GRI) benchmark list. The communication levels of the main social and environmental categories range from 31.1% for product responsibility issues to 56.7% for labour items. Yet, contentious labour concerns such as health and safety issues and employee turnover data decrease dramatically. Multiple regression analysis finds no support for the legitimacy theory hypotheses that size and profit will affect social and environmental disclosures. Instead, there seems to be more subtle changes in disclosure patterns with less transparency on controversial labour issues perhaps somewhat masked by the substitution of other less worrisome topics.